Acute abdomen in pregnancy, don't forget colonic cancer - Wong Winn Lung; Dharmendra Ganasagaran (Barpeta Obstetrics and Gynaecological Society, 2022)
Colonic cancer is rare during pregnancy. Clinical manifestation of left sided colonic tumour usually resulted in some degree of altered bowel habit. Early diagnosis is difficult as other clinical manifestation of colorectal cancer, such as constipation, abdominal pain or distension are often attributed in normal pregnancy or other gynecological pathology. Here we reported a case of young lady who presented with acute abdomen during pregnancy requiring surgery. She made good recovery post operatively and followed up post chemotherapy.